PENINGKATAN PRESTASI BELAJAR MATERI MENGATASI STRES DAN DEPRESI MELALUI BIDANG BIMBINGAN PRIBADI SOSIAL DENGAN LAYANAN BIMBINGAN KELOMPOK - Sutopo Sutopo (MEDIA DIDAKTIKA, 2015)
School as one of the institutions of formal education had a very important role in the effort to mature child and make it as useful members of society. It meant that schools also contribute to the achievement of an objective responsibility,which had been set. It should be understood that each individual had a different character that nobody has a rapid absorption of there being no lower. Owing to the difference was what can cause problems of learning difficulties, while good students will be bored when the learning process is similiar with the students who has slow learning or learning difficulties. The research used classroom action research . Services in group to improve learning achievement in the field of personal and social guidance on the eleventh graders of Social 1 SMA Negeri 1 Sekaran Lamongan in the academic year 2015/2016. Based on the data analysis, it was obtained by the activity of the students in the process of counseling services that most dominant group is working by using the tool or media, listen to or pay attention to the teacher's explanation and discussion among students or between students and teachers. So it could be said that the students activity can be considered active.